Pemanfaatan Teknologi Artificial Intelligence (AI) Interaktif Untuk Meningkatkan Kualitas Pembelajaran Anak Usia Dini Di PKG Kolase Kecamatan Kramatwatu Kabupaten Serang - Junaedi, Edi; Hidayat, Amat; Mutoharoh, Mutoharoh; Junedi, Beni; Elinawati, Elinawati; Baqi, Fuad Abdul; Rohmiyati, Yuli (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The sophistication of digital technology has presented new opportunities in early childhood education, one of which is through the use of interactive Artificial Intelligence (AI). This Community Service (PKM) activity aims to introduce and train educators at the Early Childhood Education (PKG) Kolase in Kramatwatu District, Serang Regency, in integrating AI technology into early childhood learning processes. The PKM implementation method included initial observation, hands-on training, mentoring in the use of educational AI applications, and evaluation of the training outcomes. The activity results showed that the educators were highly enthusiastic and capable of operating several developmentally appropriate AI applications, such as interactive voice-based story apps, smart educational games, and AI-based literacy and numeracy support platforms. The application of interactive AI has been proven to increase children's engagement in learning, spark curiosity, and provide a fun and adaptive learning experience. This activity has a positive impact on the quality of learning and enhances teachers' digital competency in responding to the challenges of the technological era. Therefore, the use of interactive AI technology can be an innovative solution to improve the quality of early childhood education in the future.